Evaluation of relationship between aerobic fitness level and range of isocapnic buffering periods during incremental exercise test - Algul, S.; Ozcelik, O.; Yilmaz, B. (Cellular and Molecular Biology, 2017)
The purpose of this study is to examine the relationship between the amount of O2 uptake (VO2) in the range of isocapnic buffering (ICB) periods and aerobic fitness levels of subjects with different exercise tolerance levels. A total of 50 young male subjects (20.8±0.4 years) performed an incremental exercise test using a cycle ergometer to determinetheir anaerobic threshold (AT), respiratory compensation point (RCP) and maximal exercise capacity (Wmax). The ICB period is defined as the region between AT and RCP. Pulmonary gas exchange parameters were measured breath-by-breath using a respiratory gas analyser. The subjects’ fitness levels, as indicated by peak O2 uptake to body weight ratios (VO2peak/BW), ranged from 28 ml/min/kg to 58 ml/min/kg, and Wmax capacity to body weight ratio (Wmax/BW) ranged from 1.94 W/min/kg to 3.96 W/min/kg. The VO2 in the range of ICB periodsranged from 101 ml to 793 ml (with an average of 295±157 ml). There was a positive linear correlation between VO2peak/BW, Wmax/BW and range of ICB: R=0.76542 (p<0.0001), and R=0.92135 (p<0.0001), respectively. The results of this study suggest that the range of ICB periods may be related to aerobic fitness. Importantly, aerobic fitness levels should be evaluated and considered important data, in addition toAT, VO2peak/BW and Wmax/BW.